The Sun 15 April 2010 - Zakiah Koya; AruKesamy, Karen (Sun Media Corporation Sdn Bhd, 2010)
There are 17 orang asli villages in the parliamentary constituency of Hulu Selangor. A number of them were previously situated along Sunga Selangor but they were relocated when the Ampangan Pecah Dam was constructed in 2000. Most are from the Temuan tribe.